Brown sugar babe - Sherman, Charlotte Watson, 1958- (Boyds Mills Press, an imprint of Boyds Mills & Kane, 2020)
"When a little girl has doubts about the color of her skin, her mother shows her all the wonderful, beautiful things brown can be! This message of self-love and acceptance uses rich, dreamy illustrations to celebrate the color using all the senses: sight, smell, touch, taste, and hearing" --